2008
DOI: 10.1142/s0218810408003748
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Causes and Treatment Outcome of Chronic Wrist Pain After Distal Radial Fractures

Abstract: Healed distal radial fractures are frequently complicated by chronic wrist pain which is multifactorial and can be debilitating. An accurate delineation of the pathoanatomy is the key for successful treatment. This study reviewed 22 patients who had surgical treatment between 1997 and 2001 for chronic wrist pain after distal radial fracture. Four patterns of pathoanatomy were identified: (1) ulnar impaction caused by radial malunion and shortening; (2) ulnar styloid non-union; (3) triangular fibrocartilage com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Furthermore, several authors have identified DRUJ instability as a poor prognostic factor in DRFs (Cheng et al, 2008;Geissler et al, 1996;Lindau et al, 2000b). Following on from this, Ruch et al reported that arthroscopic TFCC repair and 3 weeks of immobilization in supination in conjunction with external fixation of the DRF, resulted in no ulnar-sided wrist pain (Ruch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several authors have identified DRUJ instability as a poor prognostic factor in DRFs (Cheng et al, 2008;Geissler et al, 1996;Lindau et al, 2000b). Following on from this, Ruch et al reported that arthroscopic TFCC repair and 3 weeks of immobilization in supination in conjunction with external fixation of the DRF, resulted in no ulnar-sided wrist pain (Ruch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 A malunion may cause pain, reduced motion, reduced grip strength, carpal instability, and, eventually, osteoarthritis. [2][3][4] Sometimes, a corrective osteotomy is performed to reduce the pain and improve function. The goal of the osseous correction is to restore normal relations in the distal radioulnar joint.…”
mentioning
confidence: 99%
“…6,[11][12][13][14][15][16][17] The general consensus is that fractures involving the tip or the waist of the ulnar styloid should be treated nonsurgically because the nonunion is usually asymptomatic, but whether basal ulnar styloid fractures should be treated surgically or not is still controversial. 6,[11][12][13][14][15][16][17] The general consensus is that fractures involving the tip or the waist of the ulnar styloid should be treated nonsurgically because the nonunion is usually asymptomatic, but whether basal ulnar styloid fractures should be treated surgically or not is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…6,[11][12][13][14][15][16][17] The general consensus is that fractures involving the tip or the waist of the ulnar styloid should be treated nonsurgically because the nonunion is usually asymptomatic, but whether basal ulnar styloid fractures should be treated surgically or not is still controversial. 10,16 Fractures at the base of the ulnar styloid with substantial displacement (defined as >2 mm) have been proposed to be risk factors for the development of DRUJ instability. [17][18][19][20] In contrast, nonunion or malunion have been reported to cause DRUJ instability due to concomitant triangular fibrocartilage complex injury.…”
Section: Discussionmentioning
confidence: 99%